The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1160/th17-03-0149
|View full text |Cite
|
Sign up to set email alerts
|

Acute Haemarthrosis in the Haemophilia A Rat Generates a Local and Systemic Proinflammatory Response

Abstract: Replacement therapy with coagulation factor VIII (FVIII) concurrent with bleeds (on-demand) in haemophilia A (HA) patients has been hypothesized to increase the risk for antidrug antibodies (inhibitors). A danger signal environment, characterized by tissue damage and inflammation at the site of a bleed, is thought to contribute to the anti-FVIII response. The nature of this inflammatory reaction is, however, not fully known, and new insights will be valuable for both managing inhibitors and understanding arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
2
9
0
Order By: Relevance
“…The inhibitor levels were significantly higher after a knee bleed. These data show that in rats FVIII replacement at the time of a joint bleed potentiates inhibitor development, and this is possibly due to the systemic inflammatory response induced by the bleed [72]. In human, similar such controlled studies are yet to be reported.…”
Section: Vaccination and Infectionmentioning
confidence: 65%
“…The inhibitor levels were significantly higher after a knee bleed. These data show that in rats FVIII replacement at the time of a joint bleed potentiates inhibitor development, and this is possibly due to the systemic inflammatory response induced by the bleed [72]. In human, similar such controlled studies are yet to be reported.…”
Section: Vaccination and Infectionmentioning
confidence: 65%
“…In addition, previous studies have shown that in haemophilic rodent models, an induced joint bleed elicits a local and systemic angiogenic stimulus and upregulation of pro-inflammatory cytokines. 5,29,36 Thus, it cannot be ruled out that contralateral cartilage damage is induced by systemic modulators induced by the joint bleed. Moreover, neurogenic inflammation has been suggested as a cause of contralateral damage.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, iron-laden synovial tissue produces various inflammatory cytokines promoting the proliferation of fibroblast-like synoviocytes, which are considered key players of joint inflammation and destruction through the aggressive invasion of the extracellular matrix and production of proinflammatory mediators and cartilage-degrading enzymes [3,4,8,9]. Studies on animal models have recently helped to shed some light on the underlying pathobiology driving hemarthrosis toward HA [14,15]. A rapid in vivo proinflammatory response characterized by both local and systemic innate inflammatory mediators has been demonstrated following acute hemarthrosis in hemophilic rats [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on animal models have recently helped to shed some light on the underlying pathobiology driving hemarthrosis toward HA [14,15]. A rapid in vivo proinflammatory response characterized by both local and systemic innate inflammatory mediators has been demonstrated following acute hemarthrosis in hemophilic rats [14]. In particular, gene expression analysis revealed increased synovial fluid levels of multiple proinflammatory mediators, such as interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α, while plasma analysis demonstrated significantly increased systemic levels of IL-6 [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation